Development in Test and Evaluation of Armaments - Appavuraj, R. (Defence Science Journal, 2014)
Proof & Experimental Establishment (PXE) is the premier DRDO Artillery Firing Range located along east coast of Odisha, covering 50kms along coast and around 40kms into area with various Range Infrastructure built around 3 Firing Points to conduct Artillery weapon firing for fulfilling services requirement and R&D developmental activity. Ordnance factories, Public sector units and sister DRDO laboratories are primary users of this Firing Range. DGQA sentences the production lots based on results compiled by PXE. In order to fulfill the production target as well as various other DRDO, OFand PSU’s development trials, dedicated scientific and service community of PXE play untiring role by meticulously planning, executing various trials successfully. This special issue of Defence Science Journal on of futuristics development in Test & Evaluation of armamentscovers in total 9 technical papers that highlight primarily PXE R&D activity/developmental task for fulfilling dynamic evaluation of present and future Artillery Weapons. Defence Science Journal, Vol. 64, No. 6, November 2014, pp.497, DOI:http://dx.doi.org/10.14429/dsj.64.8107